Superficial fungal infections. (November 2017) - Hay, Roderick
Abstract: Superficial fungal infections or mycoses are common treatable conditions seen in everyday clinical practice, although they can present differently in immunosuppressed patients. Dermatophyte or ringworm infections, superficial candidiasis of the mouth, skin or genital tract and infections caused by Malassezia, such as pityriasis versicolor, are the main conditions. Although they present with typical clinical changes, diagnosis can generally be confirmed by direct microscopy or culture of suitable samples. Treatment largely depends on the use of azole (imidazole/triazole) or allylamine antifungals, applied in short courses topically or for longer periods orally, depending on the site and severity of the infection.